La plateforme numérique de MaaS HVV switch à Hambourg : un nouvel instrument de gouvernance de la mobilité ? - Manon Eskenazi; Thomas Quillerier (Netcom)
Over the last ten years or so, Hamburg's public authorities have seen the emergence of new private operators in the mobility field: digital shared mobility platforms. In an attempt to regulate them, public authorities embraced the concept of Mobility as a Service (MaaS) by creating the Switchh platform in 2013, backed up by “mobility stations” deployed in public spaces. This article looks at how the city of Hamburg is using MaaS as an instrument to i) organise this new ecosystem of mobility stakeholders and ii) transform public space to meet its sustainable mobility objectives. Our qualitative study, based on semi-structured interviews, documents analysis and observation, shows that the public authorities are taking advantage of MaaS as a tool for coordinating players, via the city's public transport operator. However, the public sector's lack of human and financial resources, coupled with the neo-liberal interests of private operators in a freely competitive market, has led to the privatisation of Hamburg's public space through MaaS, and calls into question its social effects.